1917 Minn. Gen. Laws 354, Sess. Laws, ch. 244, § 1 - (:unkn) unknown (General Publisher, 1917)
Every person who shall manufacture, or cause to be manufactured, sell, keep for sale, offer, or dispose of, any instrument or weapon of the kind usually known as a slung-shot, sand-club, or metal knuckles; or who shall attempt to use against another, or with intent so to use, shall carry, conceal, or possess, any of the weapons hereinbefore specified, or any dagger, dirk, knife, pistol, or other dangerous weapon, shall be guilty of a gross misdemeanor. The possession by any person, other than a public officer, of any such weapon concealed or furtively carried on the person shall be presumptive evidence of carrying, concealing, or possessing with intent to use the same.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS